Sintomatologia depressiva em idosos residentes na comunidade: prevalência e associação com atividade física e o comportamento sedentário - MENEGUCI, Joilson (2018)
With the increasing number of older adults in Brazil and the consequences of depressive symptoms in this population segment, knowledge of the prevalence and the effect of the mediators on its relation with the behaviors may contribute to understanding the explanatory mechanisms of the disease. Thus, we developed the current project in two parts: 1) a systematic review with meta-analysis to estimate the prevalence of depressive symptoms for Brazilian community-dwelling older adults; and 2) a population-based cross-sectional study to: a) identify the prevalence and factors associated with depressive symptoms in the elderly; b) to evaluate the direct and indirect associations of physical activity and sedentary behavior with depressive symptoms in the elderly; c) to examine the hypothetical effects of substitution of sleep time, sedentary behavior and moderate to vigorous physical activities (MVPA) on depressive symptoms in the elderly. For the systematic review, we searched the electronic databases Medline (via PubMed), SciELO, Web of Science, Scopus and CINAHL, and also selected studies with Brazilian elderly people that identified the prevalence of depressive symptoms. The meta-analysis was performed to estimate the prevalence of depressive symptoms using a random effect model. The heterogeneity of results was assessed by the chi-square test (significance at p<0.10) while magnitude of effects was quantified by I2. The second study was conducted with 473 elderly enrolled in the Family Health Strategy and living in the urban area of the city of Alcobaça, State of Bahia. Older adults who met the study criteria and gave their consent to participate answered an interview-based structured questionnaire, containing questions on sociodemographic, health and behavioral issues. Depressive symptoms were assessed with the short version of the Geriatric Depression Scale. Multiple Correspondence Analysis, Path Analysis and Isotemporal Replacement Approach were applied in Poisson Regression models for analyzing the data. According to the meta-analysis, the estimated prevalence of depressive symptoms for Brazilian community-dwelling older adults was 21.0% (95%CI: 18.0-25.0, I2 = 98.3%). Conversely, our cross-sectional study indicated a prevalence of 11.8% (95%CI: 9.2- 15.1) for depressive symptom in older adults from Alcobaça, BA. The profile of the elderly with depressive symptoms was characterized mainly by health and behavioral aspects. Physical activity had an indirect association with depressive symptoms, beingmediated by self-esteem and functional capacity. The association of sedentary behavior with depressive symptoms was mediated by functional capacity and sleep quality. In the analyzes of the isotemporal models, it was verified that replacing the time spent sitting for the same amount of time in sleep or moderate and vigorous activities can lead to benefits for depressive symptoms. The longer the time replaced, the greater the protective effect found. The replacement of sitting time by MVPA resulted in greater reductions of depressive symptoms. The results of the present study indicate the need for intervention strategies to reduce the prevalence of depressive symptoms. When considering interventions related to physical activity and the reduction of sedentary behavior towards depressive symptoms, functional capacity, self-esteem and sleep factors are taken into account as mediators.